Consumer Protection against Overclaim of Skincare Products: A Comparison of Regulations of BPOM Indonesia and the Ministry of Food and Drug Safety of South Korea - Amina, Frahnaz; Tarina, Dwi Desi Yayi (UNIVERSITAS PAKUAN, 2025)
AbstractThe development of the skincare industry in Indonesia has been accompanied by increasing overclaiming practices, indicating a legal loophole in consumer protection through regulation and supervision by the Indonesian Food and Drug Administration (BPOM). This study aims to compare the regulations and supervision of BPOM Indonesia and the South Korean Ministry of Food and Drug Safety (MFDS), which has a strong mechanism for regulating and supervising cosmetic products. The method used is normative juridical with a legislative, case, and comparative approach, through a literature study and descriptive analysis. The results show that BPOM's regulation of claims is still general and does not distinguish between general and functional cosmetics, does not set detailed scientific standards for proving claims, and supervision is reactive. On the contrary, South Korea's MFDS has implemented cosmetic classification, scientific evidence standards for claims, and proactive risk-based oversight. Therefore, BPOM is advised to clarify cosmetic classification, establish scientific evidence standards for claims, and develop an Integrated Digital Monitoring Framework System to strengthen proactive digital oversight and consumer protection. Keywords: Comparative Law, Consumer Protection, Overclaim.